Fe3O4Nanoparticles Grown on Cellulose/GO Hydrogels as Advanced Catalytic Materials for the Heterogeneous Fenton-like Reaction - Chen, Yian; Potschke, Petra; Pionteck, Jurgen; Voit, Brigitte; Qi, Haisong (ACS Omega, 2019)
Cellulose/graphene oxide (GO)/iron oxide (Fe 3 O 4 ) composites were prepared by coprecipitating iron salts onto cellulose/GO hydrogels in a basic solution. X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared, and X-ray diffraction characterization showed that Fe 3 O 4 was successfully coated on GO sheets and cellulose. Cellulose/GO/Fe 3 O 4 composites showed excellent catalytic activity by maintaining almost 98% of the removal of acid orange 7 (AO7) and showed stability over 20 consecutive cycles. This performance is attributable to the synergistic effect of Fe 3 O 4 and GO during the heterogeneous Fenton-like reaction. Especially, the cellulose/GO/Fe 3 O 4 composites preserve their activity by keeping the ratio of Fe 3+ /Fe 2+ at 2 even after 20 catalysis cycles, which is supported by XPS analysis.
CRIS-Team Scopus Importer:2022-04-14